KEAMANAN JARINGAN DENGAN PACKET FILTERING FIREWALL (STUDI KASUS: PT. SUKSES BERKAT MANDIRI JAKARTA) - Siti Nur Khasanah (Universitas Bina Sarana Informatika, 2016)
Network security is currently a very important issue and continues to grow. Development of computer technology, besides causing many benefits also have many bad side. One of them is an attack on computer systems connected to the Internet. As a result of the attack, many computer systems or networks disrupted even be damaged. Given these problems, then as soon as possible we must immediately secure computer networks from attack. Untangle is a Linux distribution that is used as a regulator of tissue. Untangle is an open source first terintegerasi to deal with spam, spyware, viruses, adware, web-filtering and report. Based on Debian Linux with supporting JAVA applications. Untangle Server delivers the ease in securing, controlling and monitoring of computer networks. Ease is a technology that is needed to secure from threats such as viruses and spyware, web access and control over the availability of the report of the Untangle Server to perform a system analysis. Everything is packaged within an interface / GUI (Graphical User Interface). Untangle is very handy and has a full feature in managing and securing the network from LAN to WAN scale.Keywords: Network Security, Packet Filtering Firewall, Untangle